PENERAPAN BELAJAR AKTIF MAHASISWA DI PERGURUAN TINGGI DENGAN MENGUNAKAN PENDEKATAN CONSTRUCTIVISM - Istiqlal, Abdul (EDUTECH CONSULTANT, 2018)
This study aims to describe and to know the implementation of learning model with active learning with constructivism approach in higher education at STKIP Ahlussunah Bukittinggi. The population of the research was the fourt semester students of STKIP Ahlussunnah bukittinggi on 2016/2017. The sampel number of the student is 38 people. The instrument of this research is the aouthorâ€s own and performance tests. This research data analyzed by using qualitative method and deep appreciation of the phenomenon that accurs. The results of this study can be concluded that the application and implementation of active learning and constructivism approach at higher education that succes. This research is very useful for teacher/lecture and student in improving the guality of teaching and learning process and learning outcomes of students.. The results of the research showed that student who were taught by using the active learning and constructivism approach at higher education, outcomes learning achievement than students who were taught by using a conventional approach at STKIP Ahlussunnah Bukittinggi.